Edukasi Pilar Sanitasi Total Berbasis Masyarakat Di Desa Notorejo, Kabupaten Tulungagung - Drastyana, Serlly Frida; Prasetyorini, Anif; Sutha, Diah Wijayanti; Ali, Amir (Jurnal Abdimas Jatibara, 2024)
One of the efforts made by the government in improving the sanitation status of the community is the STBM (Community Based Total Sanitation) Program. Tulungagung Regency has been designated as the 22nd Regency / City in East Java Province that is Open Defecation Free (ODF), but the verifier team still found around 1.3% of Tulungagung residents who do not have safe latrines and 7% of Tulungagung residents who still share latrines with other families. The purpose of this activity is to increase the knowledge of mothers of infants and toddlers about the pillars of community-based total sanitation in Notorejo Village, Tulungagung Regency. The method used in the implementation of activities in February 2024. The activity method is in the form of exposure to counseling material. question and answer and pre and post test measurements. The results of community service obtained that there is an increase in knowledge after counseling mothers of infants and toddlers about the pillars of community-based total sanitation. Further evaluation can be carried out to measure the extent to which the increase in knowledge brings changes in the sanitation behavior of the local community.